2012
DOI: 10.5539/jas.v4n2p79
|View full text |Cite
|
Sign up to set email alerts
|

Development of Farmer-led Integrated Management of Major Pests of Cauliflower Cultivated in Rainy Season in India

Abstract: Implementation of Integrated Pest and Disease Management programme in irrigated cauliflower crop led to reduction in number of conventional pesticide sprays by 50-60 %. The safer biorational pesticides, insect growth regulators and cultural methods of pest management as introduced in the IPM programme were well received by the farmers in farmers' participatory trainings (FPT). Lower insect and disease incidence with higher curd production was observed in the IPM fields as compared to conventional non IPM field… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
12
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 18 publications
5
12
0
Order By: Relevance
“…Trichoderma harzianum (Th3) was found to effectively control the Groundnut root rot epidemic (Kalijad disease) in Rajasthan. The bioefficacy of Th3 strain has already been tested in different crops like cauliflower, cabbage, chilli, tomato, and against a large number of soil and foliar pathogens namely Pythium aphanidermatum, Phytophthora parasitica, Fusarium oxysporum, Sclerotinia sclerotiorum, Sclerotium rolfsii, Phomopsis vexans, Alternaria alternata, Rhizoctonia solani, Colletotrichum capsici (Ahuja et al, 2012;Sharma et al, 2001Sharma et al, , 2003Sharma et al, , 2006Sharma & Dureja, 2004;Sharma & Sain, 2004Qais et al, 2005). Effective bio-formulation of the Trichoderma harzianum (Th3) strain was formulated and validated (Sharma and Sain, 2003 a & b).…”
Section: Discussionmentioning
confidence: 99%
“…Trichoderma harzianum (Th3) was found to effectively control the Groundnut root rot epidemic (Kalijad disease) in Rajasthan. The bioefficacy of Th3 strain has already been tested in different crops like cauliflower, cabbage, chilli, tomato, and against a large number of soil and foliar pathogens namely Pythium aphanidermatum, Phytophthora parasitica, Fusarium oxysporum, Sclerotinia sclerotiorum, Sclerotium rolfsii, Phomopsis vexans, Alternaria alternata, Rhizoctonia solani, Colletotrichum capsici (Ahuja et al, 2012;Sharma et al, 2001Sharma et al, , 2003Sharma et al, , 2006Sharma & Dureja, 2004;Sharma & Sain, 2004Qais et al, 2005). Effective bio-formulation of the Trichoderma harzianum (Th3) strain was formulated and validated (Sharma and Sain, 2003 a & b).…”
Section: Discussionmentioning
confidence: 99%
“…In Northern India, nine species of insects and four diseases are considered important. Insects limiting cauliflower production include aphids (Myzus persicae (Ahuja et al, 2012(Ahuja et al, , 2013. Four major diseases include Sclerotinia rot (Sclerotinia sclerotiorum [Lib.…”
Section: Introductionmentioning
confidence: 99%
“…It concluded that about 82 percent of the vegetable growers had low or medium adoption of commercial potato cultivation practices and means that medium adopters have more interest in adoption of new and beneficial methods. Ahuja et al (2012) implemented Integrated Pest and Disease Management programme in irrigated cauliflower crop which led to reduction of 50-60% in the number of conventional pesticide sprays. The use of less or required pesticide application was reinforced by enemies resulting in sustainable and stable pest control regime.…”
Section: Introductionmentioning
confidence: 99%